2009
DOI: 10.1002/rcm.3943
|View full text |Cite
|
Sign up to set email alerts
|

Bronze Age volcanic event recorded in stalagmites by combined isotope and trace element studies

Abstract: Stable isotope analyses of speleothems (carbonate deposits formed in caves) have been widely used to reconstruct paleoenvironmental conditions. Recent improvements in geochemical techniques have enabled us to analyze climate‐influenced deposits at high temporal resolution so that hitherto unrecognized environmental conditions may be identified. Stable H, C and O isotope analyses on carbonate and inclusion water have been combined with multicollector inductively coupled plasma mass spectrometry (MC‐ICP‐MS) age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
0
41
0
1
Order By: Relevance
“…This of course includes modern day semi-arid and arid climate regions, as well as regions which have experienced past aridity in the Quaternary or older time periods. Our results will therefore facilitate the interpretation of speleothem trace element records from regions such as Israel (Bar Matthews et al, 1991), Yemen (Van Rempelbergh et al, 2013), Turkey (Siklósy et al, 2009) and Morocco (Wasserburg et al, 2013), as well as from Australia (McDonald et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…This of course includes modern day semi-arid and arid climate regions, as well as regions which have experienced past aridity in the Quaternary or older time periods. Our results will therefore facilitate the interpretation of speleothem trace element records from regions such as Israel (Bar Matthews et al, 1991), Yemen (Van Rempelbergh et al, 2013), Turkey (Siklósy et al, 2009) and Morocco (Wasserburg et al, 2013), as well as from Australia (McDonald et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…Trace element variability in speleothems from the region provided basis for paleohydroclimate implications [10][11][12], supported the identification of historical flood events [13]. Siklósy et al [14] associated a sudden rise in rare earth elements with the Middle Bronze Age eruption of Santorini. In the meanwhile, changes in U concentration and δ 234 U changes associated with an increase in detrital material (e.g.…”
Section: Introductionmentioning
confidence: 81%
“…Despite the potential of inclusion fluid research, stable isotope compositions of fluid inclusions have only been gathered from Turkish and Hungarian speleothems from the Eastern Europe & Turkey region. Hydrogen isotope compositions of inclusion-hosted water, analyzed by the continuous flow technique [19] for a stalagmite from SE Hungary was interpreted as a sign of drip water composition variation in the Bronze Age [14]. Although the analytical precision and post-deposition exchange processes precluded precise paleotemperature calculations, the co-variation of δ 18 O for speleothem calcite and inclusion-hosted water analyzed in a stalagmite from Eastern Turkey were used to infer past variations in seasonal precipitation distribution [20].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is one of the characteristic and abundant elements in igneous rocks, with a mass fraction range of 10 3 -10 4 μg/g (Nockolds, 1954). Al has been used as a trace indicator for volcanic events recorded in carbonates (Siklósy et al, 2009;Wu et al, 2018). Laboratory experiments demonstrated that high amounts of aluminum can be released when tephra enters surface seawater (Frogner Kockum et al, 2006).…”
Section: Decipher Possible Sources Of Ree Anomaliesmentioning
confidence: 99%